A Basis for Positivist and Political Public Law: Reconciling Loughlin's Public Law with (Normative) Legal Positivism. (1st September 2016) - Gordon, Michael
Abstract : This article analyses the work of Martin Loughlin on the nature of public law, and in particular, his ostensibly strident anti-positivism. It is argued that despite this, Loughlin's work can be reconciled with a normative account of legal positivism, based on the work of Jeremy Waldron. The article maintains that Loughlin's account of public law as political jurisprudence is methodologically compatible with, and potentially even substantively complementary to, normative legal positivism. It is ultimately suggested that this reconciliation provides a methodology for public law scholarship which is both positivist and political, and which may offer insight into the subject beyond that which either approach might generate alone.